2018
DOI: 10.1111/jam.14130
|View full text |Cite
|
Sign up to set email alerts
|

An indigenous strain of potassium-solubilizing bacteria Bacillus pseudomycoides enhanced potassium uptake in tea plants by increasing potassium availability in the mica waste-treated soil of North-east India

Abstract: Aim: Potassium (K) is one of the three major nutrients required of plant growth and muriate of potash (MoP) is the only recognized chemical fertilizer used in agriculture. In many countries, 100% of the applied MoP is imported costing huge revenue. Application of suitable potassium-solubilizing bacteria (KSB) as biofertilizer could be an integral part of K management in arable soil. The object of this study was to evaluate K-solubilizing ability of a ubiquitous micro-organism as KSB to supplement K in soil. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…KSB are often applied with a mineral form of potash like mica waste. Recently B. pseudomycoides , a KSB, was isolated from tea‐growing soils of North east India and was found to increase the availability of potassium in soil and uptake in tea plants when inoculated with Mica waste (Pramanik et al ). Another important nutrient where Bacillus can be found to play a major role is zinc.…”
Section: Role Of Bacillus In Potassium and Other Nutrients Uptakementioning
confidence: 99%
“…KSB are often applied with a mineral form of potash like mica waste. Recently B. pseudomycoides , a KSB, was isolated from tea‐growing soils of North east India and was found to increase the availability of potassium in soil and uptake in tea plants when inoculated with Mica waste (Pramanik et al ). Another important nutrient where Bacillus can be found to play a major role is zinc.…”
Section: Role Of Bacillus In Potassium and Other Nutrients Uptakementioning
confidence: 99%
“…B. mucilaginosus, when inoculated in soil, improved the oil content and groundnut biomass by 35.4% and 25%, respectively, along with enhanced K and P availability [93]. Recently, a study has shown that a potassium-solubilizing strain Bacillus pseudomycoides enhanced K uptake in tea plants in the mica waste-treated soil by increasing potassium availability [94]. Another strain Bacillus cereus significantly increased the plant height, shoot dry weight, and branches number by about 15%, 26%, and 27%, respectively, compared to the control [95].…”
Section: Potassium Solubilizing and Mobilizing Biofertilizersmentioning
confidence: 99%
“…Most of these Bacillus spp. are associated with plants and were reported to have potential application in biomedicine and biocontrol (Liu et al, 2019;Lu et al, 2017;Jouzani et al, 2017;Prazdnova et al, 2019;Wang et al, 2017) as well as potential probiotics (Elshaghabee et al, 2017) and biofertilizer (Pramanik et al, 2019). Lysinibacillus and Paenibacillus are widespread bacteria usually considered as environmental contaminants and rarely connected to human diseases (Wenzler et al, 2015;Sannino and Angert, 2017).…”
Section: Microbial Ecology In Pot-pollen Samplesmentioning
confidence: 99%